2022
DOI: 10.1111/een.13177
|View full text |Cite
|
Sign up to set email alerts
|

Developmental temperature predicts body size, flight, and pollen load in a widespread butterfly

Abstract: Most of our understanding of the effects of climate warming on insect body size comes from laboratory experiments. Whether these studies predict patterns in nature is largely unknown. Here we examine the relevance of laboratory warming experiments for wild populations of the butterfly Pieris rapae. We tested two predictions: (i) butterflies reared at warmer temperatures in the laboratory should attain smaller adult sizes and have reduced flight ability, and (ii) in nature, this trait combination should lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
5
4
1
Order By: Relevance
“…We found no effect of wing size on flight metrics, nor did the data suggest a relationship between food type and wing size. Our results conflict with the findings of previous studies, which have found a positive correlation between wing size and flight metric performance in both lab-reared and wild-caught monarchs (Büyükyilmaz & Tseng, 2022).…”
Section: Resultscontrasting
confidence: 99%
“…We found no effect of wing size on flight metrics, nor did the data suggest a relationship between food type and wing size. Our results conflict with the findings of previous studies, which have found a positive correlation between wing size and flight metric performance in both lab-reared and wild-caught monarchs (Büyükyilmaz & Tseng, 2022).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to such expectations, the flight of spring Pieris was significantly slower than that of summer individuals (Table 2). A lower flight speed in smaller individuals of P. rapaealbeit showing higher wing loadingwas also observed by Büyükyilmaz & Tseng (2022), who used a flight mill to measure velocity and covered distance of those butterflies. Similarly, Almbro and Kullberg (2012) noted that larger wing loading is associated with reduced flight speed in P. napi males, but not in females.…”
Section: Seasonal But Not Interspecific Morphological Differences Aff...supporting
confidence: 60%
“…Larval growth is affected by host plant species and their quality (Hwang et al, 2008), by ambient temperatures and photoperiod (Nylin, 1994). Low ambient temperatures experienced by immatures lead to the development of larger adult individuals of summer form, which may indirectly influence their faster flight compared to smaller individuals reared in colder conditions (Büyükyilmaz & Tseng, 2022). Shortening days towards the end of summer and autumn stimulate the initiation of the overwintering stage, pupae, resulting in smaller spring individuals (Wiklund et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there has been increasing interest in the effects of recent climate change on ectotherm body sizes (Daufresne et al., 2009; Scaven & Rafferty, 2013; Sheridan & Bickford, 2011). Several lines of evidence support the predictions of the temperature‐size rule, including controlled warming experiments (Büyükyilmaz & Tseng, 2022; Culler et al., 2015; Frouz et al., 2002; McCauley et al., 2015; Wonglersak et al., 2021), biogeographic comparisons of body size across latitudes (Baranov et al., 2022; Hassall, 2013; but see Shelomi, 2012), and comparisons between cohorts of multivoltine insects emerging at different times of the year (Horne et al., 2017). A meta‐analysis of warming experiments shows that one degree of warming can result in up to a 2.6% decrease in arthropod body size, although most changes are between 0.2% and 1.5% (Klok & Harrison, 2013).…”
Section: Introductionmentioning
confidence: 56%